Clonagem e avaliação da expressão gênica do neuropeptídeo Y no linguado Paralichthys orbignyanus - Campos, Vinicius Farias (2009)
Food intake in vertebrates is a complex process involving several endocrine and neural pathways. Among the orexigenic factors, the most notably are the neuropetides as the neuropeptide Y (NPY) that is a 36 amino acid peptide which plays a key role in food intake. Studies evaluating fish NPY expression showed that this peptide is involved in appetite stimulation. However, despite the recent advances, our present knowledge of the regulation of feeding behavior in fish is limited and based in a few fish species, and there is increasing evidence of speciesspecific differences. The Brazilian flounder Paralichthys orbignyanus is being considered for aquaculture, and it is important to understand the mechanisms regulating feeding in order to improve its performance in captivity. The objectives of this study were to clone NPY cDNA, evaluate the mRNA levels in different tissues of flounder, and also evaluate brain NPY expression during 24 h by real-time RT-PCR. A 597 bp NPY cDNA was cloned from Brazilian flounder brain by 3´RACE method. NPY expression was detected in all peripheral tissues analyzed, but with predominant expression in the brain. No significant differences were observed in brain NPY gene expression over a 24 h evaluation period. No correlation was observed among plasma glucose, total protein, cholesterol, triglycerides and NPY expression levels during 24 hours. These results indicated that NPY may play roles in flounder peripheral tissues and may be not involved short-term regulation of food intake at low-temperatures in Brazilian flounder.